Enabler of Madrasah Education: The Case of LGU-Supported Traditional Madrasah in General Santos City - Sales, Almera Mode; Alaiden, Esmaida Andang; Pantao, Jovar G. (PT. Riset Press International, 2025)
This study explored the enablers of Madrasah education programs, focusing on locally-led efforts of the Local Government Unit of General Santos to support the traditional Madrasahs in the city, recognizing the vital role of traditional madrasah education in promoting religious and cultural identity as well as social cohesion. This research analyzed the key factors contributing to these educational initiatives' effective implementation and sustainability. A case study method approach was utilized, including surveys and interviews. The findings revealed several critical enablers, such as active community involvement, government assistance, and capacity building. This paper underscores the significance of the all-of-the-community approach in creating an inclusive educational environment that meets the needs of Muslim learners. Hence, the analysis concluded that contextual factors such as social, economic, environmental, and political dimensions affect the implementation of the traditional Madrasah in General Santos City. The study recommends the standardization of the traditional Madrasah Curriculum, considering the nuances of Muslim communities in General Santos.